Right atrial hemangioma - Karaca, Ilgin; Yavuzkir, Mustafa; Ilkay, Erdo?an; Akbulut, Mehmet; Rahman, Ali; Çobano?lu, Bengü (My University, 2003)
[Abstract Not Available]
Sa? atriyal hemanjiyoma
Keywords: Diagnosis, Differential; Echocardiography; Female; Heart Neoplasms; Hemangioma; Humans; Middle Aged; cardiopulmonary bypass; cardiovascular system tumor; electrocardiography; heart right atrium; hemangioma; human; note; pathology; sternotomy; transesophageal echocardiography; transthoracic echocardiography